Characterisation of the sensory profile of Cyclopia intermedia and optimisation of fermentation parameters for improved product quality - Bergh, Alexandra Jane (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScFoodSc)--Stellenbosch University, 2014.